Polarimetric coordinate validation for merging GRASP and AirMSPI FIREX-AQ observations - DeLeon, Clarissa M.; Garay, Michael J.; Kalashnikova, Olga V.; Kupinski, Meredith K. (Journal of quantitative spectroscopy & radiative transfer, 2024)
Traditionally, aerosol retrieval algorithms are customized to specific instruments because of the diverse nature of remote sensing hardware architectures and data formats. This diversity can hinder the utilization of lower-level data products. Furthermore, a generalized aerosol retrieval approach has the potential to allow simultaneous use of observations from multiple platforms within a single retrieval framework. In this work, a comprehensive set of solutions for integrating open-source aerosol retrieval software and publicly available multiangle spectropolarimetric data products is presented as a complementary software program (CSP). This CSP is adaptable to observations obtained from various instruments, including the Airborne Multiangle Spectropolarimetric Imager (AirMSPI) and the upcoming Multiangle Imager for Aerosols (MAIA) (Diner et al., 2013); (Maia, 2022). Established methods for reconciling coordinate systems, curating data, and structuring data for input to the Generalized Retrieval of Atmosphere and Surface Properties (GRASP) open-source software are addressed by the CSP (Grasp-open, 2023).The CSP provides the functionality to compute multiple GRASP aerosol retrievals from the same polarimetric observations by varying the user-defined coordinate system selection. Each coordinate system is defined by a unique reference plane, which rotates the reported polarization orientation but does not alter the information content. Therefore retrieving aerosol values from different coordinate systems is suggested as a tool for: (1) verifying the coordinate systems of the instrument and algorithm have been properly reconciled and (2) quantifying numerical variations in the retrieval’s optimization algorithm. The CSP is demonstrated using AirMSPI data from the 2019 Fire Influence on Regional to Global Environments and Air Quality (FIREX-AQ) campaign (Diner et al., 2013); (Warneke, 2019). Aerosol retrievals performed with the meridian versus the scattering reference plane differed up to 0.068 in aerosol optical depth and 0.015 in single scattering albedo. These variations in smoke properties from multiangle spectropolarimetric observations quantify uncertainty which is applicable for cross-validation instrument comparisons and studies of different retrieval algorithms. •Polarimetric Geometry Reconciliation Validation Using Two Reference Planes.•Merging Multiangle Polarimetric Data and a Generalized Radiative Transfer Algorithm.•GRASP Aerosol Retrievals of AirMSPI FIREX-AQ Data.•Python Code to Prepare Data for GRASP Input.